Training on an Appetitive Trace-Conditioning Task Increases Adult Hippocampal Neurogenesis and the Expression of Arc, Erk and CREB Proteins in the Dorsal Hippocampus - Tripathi, Shweta; Verma, Anita; Jha, Sushil K. (Frontiers in Cellular Neuroscience, 2020)
Adult hippocampal neurogenesis (AHN) plays an essential role in hippocampal-dependent memory consolidation. Increased neurogenesis enhances learning, whereas its ablation causes memory impairment. In contrast, few reports suggest that neurogenesis reduces after learning. Although the interest in exploring the role of adult neurogenesis in learning has been growing, the evidence is still limited. The role of trace and delay appetitive-conditioning on AHN and its underlying mechanism are not known. The consolidation of trace-conditioned memory requires hippocampus, but delay-conditioning does not. Moreover, the dorsal hippocampus (DH) and ventral hippocampus (VH) may have a differential role in these two conditioning paradigms. Here, we have investigated the changes in [A] hippocampal cell proliferation and their progression towards neuronal lineage and [B] expression of Arc, Erk1, Erk2, and CREB proteins in the DH and VH after trace- and delay-conditioning in the rat. The number of newly generated cells significantly increased in the trace-conditioned but did not change in the delay-conditioned animals compared to the control group. Similarly, the expression of Arc protein significantly increased in the DH but not in the VH after trace-conditioning. Nonetheless, it remains unaltered in the delay-conditioned group. The expression of pErk1, pErk2, and pCREB also increased in the DH after trace-conditioning. Whereas, the expression of only pErk1 pErk2 and pCREB proteins increased in the VH after delay-conditioning. Our results suggest that appetitive trace-conditioning enhances AHN. The increased DH neuronal activation and pErk1, pErk2, and pCREB in the DH may be playing an essential role in learning-induced cell-proliferation after appetitive trace-conditioning.